DIGITAL INFORMATION TECHNOLOGIES AND POETICS OF CULTURE: TRANSFORMATION OF MEANINGS AND FORMS - Сумятін, Станіслав (SWorldJournal, 2025)
The article is devoted to the influence of digital information technologies on the poetics of culture, which is understood as a system of expressive means and principles of cultural organization. Particular attention is paid to changes in the forms and co